Developing Team Creativity: The Influence of Psychological Safety and Relation‐Oriented Shared Leadership. Issue 2 (30th January 2019) - Han, Soo Jeoung; Lee, Yunsoo; Beyerlein, Michael
Abstract : This study examines the effects of a psychosocially safe environment and two types of shared leadership on project team creativity. We focused on specific dimensions of shared leadership to examine their association with creative outcomes. To measure the dimensions, we conducted a survey of 260 graduate and undergraduate students working in project teams at a large Southwestern university. We found that a psychologically safe environment enabled team members to perform task‐oriented and relation‐oriented tasks. However, only relation‐oriented shared leadership positively influenced team creativity. Based on our findings, we provided research and practical implications, as well as study limitations and future research suggestions.